2009
DOI: 10.1038/modpathol.2009.76
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability, telomere shortening, and inactivation of p21WAF1/CIP1 in dysplastic nodules of hepatitis B virus-associated multistep hepatocarcinogenesis

Abstract: Systemic analysis for chromosomal instability and inactivation of cell cycle checkpoints are scarce during hepatocarcinogenesis. We studied 24 patients with chronic B viral cirrhosis including 30 cirrhotic regenerative nodules, 35 low-grade dysplastic nodules, 15 high-grade dysplastic nodules, 7 dysplastic nodules with hepatocellular carcinoma foci, and 18 hepatocellular carcinomas. Eight normal livers were studied as the control group. Telomere length and micronuclei were detected by Southern blot and Feulgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 31 publications
3
31
0
1
Order By: Relevance
“…Both hSSB1 and p21 were mainly located in the nuclei of the cancer cells and were highly expressed in the HCC tissues (Figure 6a). This result was consistent with the majority of previous studies showing that the tumor cells of HCC exhibited positive nuclear staining of p21 (Qin et al, 1998;SchonigerHekele et al, 2005;Kao et al, 2007;Lee et al, 2009). However, some reports have showed cytoplasmic p21 staining in HCC (Tanaka et al, 2002;Lee and Helfman, 2004;Shiraki and Wagayama, 2006), and we also observed a weak cytoplasmic p21 staining in three cases (3%) of HCC tissues that were excluded in our statistical analyses in this report.…”
Section: Cdt2supporting
confidence: 93%
“…Both hSSB1 and p21 were mainly located in the nuclei of the cancer cells and were highly expressed in the HCC tissues (Figure 6a). This result was consistent with the majority of previous studies showing that the tumor cells of HCC exhibited positive nuclear staining of p21 (Qin et al, 1998;SchonigerHekele et al, 2005;Kao et al, 2007;Lee et al, 2009). However, some reports have showed cytoplasmic p21 staining in HCC (Tanaka et al, 2002;Lee and Helfman, 2004;Shiraki and Wagayama, 2006), and we also observed a weak cytoplasmic p21 staining in three cases (3%) of HCC tissues that were excluded in our statistical analyses in this report.…”
Section: Cdt2supporting
confidence: 93%
“…Further, they demonstrated declining telomere lengths with neoplastic hepatocytes having the shortest telomere length. Lee et al have extended these finding in HBVassociated carcinogenesis identifying an increase in micronuclei formation, p21 inactivation and reduction in telomere length from low grade dysplastic nodules to high grade dysplastic nodules to HCC [93].…”
Section: Telomeres In Hccmentioning
confidence: 85%
“…Results of these studies indicate that histopathological or cytological examination of NPs may be used as additional biomarkers in cancer screening [28,27].…”
Section: Discussionmentioning
confidence: 99%